Nivel de conocimiento en infecciones de transmisión sexual en estudiantes del cuarto y quinto año de secundaria de tres instituciones educativas de un distrito de alta incidencia de ITS – Chiclayo 2018. - Rojas Tesen, Anthony Wilmer (2020)
Objective: Identify the level of knowledge in sexually transmitted infections in fourth and fifth year high school students from three educational institutions in a district with a high incidence of STIs - Chiclayo 2018. Materials and methods: An observational, descriptive, cross-sectional study that included 540 fourth and fifth secondary students from the schools "10836 La Aplicacion", "Cristo Rey" and "Mariano Melgar"; An anonymous data collection form was prepared and with informed consent and consent; that collected information on the general characteristics and level of knowledge in sexually transmitted infections. The results were analyzed in the statistical program Stata 14 and presented in tables and graphs. Results: The level of regular knowledge was 49.6%, followed by Low (48.1 %) and only 2.2 % obtained High knowledge. A significant difference (p <0.05) was found between the level of knowledge with sex and having received previous training. Conclusions: The most frequent level of knowledge among fourth- and fifth-year students was Regular.